2022
DOI: 10.1186/s12960-022-00767-4
|View full text |Cite
|
Sign up to set email alerts
|

A national analysis of the pharmacy workforce in Indonesia

Abstract: Background Pharmacists play a fundamental role in healthcare systems and achieving Universal Health Coverage (UHC) through quality primary healthcare service provision. While the World Health Organization (WHO) forecasts a global shortage of health workforce by 2030, mainly affecting low- and middle-income nations (LMICs), limited published literature is found regarding pharmacy workforce capacity in LMICs, including Indonesia. This paper aims to analyse pharmacists’ capacity in Indonesia to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
2
5
0
Order By: Relevance
“…Thus, our finding of the low involvement of pharmacists in this type of care is plausible. A national study showed that young female pharmacists are more likely to engage in patient-centred activities,23 which might be the case for TB care, as we also found a higher proportion of young females (in their 30s) than male pharmacists working in hospitals, that is in line with that study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, our finding of the low involvement of pharmacists in this type of care is plausible. A national study showed that young female pharmacists are more likely to engage in patient-centred activities,23 which might be the case for TB care, as we also found a higher proportion of young females (in their 30s) than male pharmacists working in hospitals, that is in line with that study.…”
Section: Discussionsupporting
confidence: 91%
“…Several strengths and limitations should be noted. A strength was the nationwide survey in Indonesia based on the sampling adequacy and participating pharmacist workforce proportion 23. The survey was extensively validated and reported according to the CHERRIES checklist.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the proportion of female pharmacy students (74.4%) is higher than male pharmacy students (16.6%) in this study which is in line with national data showing that females will represent around 86% of pharmacists in Indonesia by 2030 [ 28 ]. We further observed that the level of knowledge of telepharmacy among pharmacy students in this study is lower than those of pharmacy students in Malaysia [ 21 ] and the USA [ 29 ] in which majority of the respondents also female pharmacy students.…”
Section: Discussionsupporting
confidence: 89%
“…However, the issue extends beyond mere numbers; the distribution of these workers plays a critical role in ensuring that all regions, irrespective of their geographic or demographic characteristics, have access to adequate healthcare services. This challenge is further compounded by the issue of healthcare workforce production in Indonesia, which is not accompanied by equitable distribution [8][9][10] . The imbalance in the distribution of health workers, particularly in a geographically diverse country like Indonesia, presents a multifaceted challenge that needs comprehensive analysis and targeted interventions 11 .…”
Section: Introductionmentioning
confidence: 99%